Novel opportunities for wildlife conservation and research with real‐time monitoring. Issue 4 (1st June 2014) - Wall, Jake; Wittemyer, George; Klinkenberg, Brian; Douglas-Hamilton, Iain
Abstract : The expansion of global communication networks and advances in animal‐tracking technology make possible the real‐time telemetry of positional data as recorded by animal‐attached tracking units. When combined with continuous, algorithm‐based analytical capability, unique opportunities emerge for applied ecological monitoring and wildlife conservation. We present here four broad approaches for algorithmic wildlife monitoring in real time—proximity, geofencing, movement rate, and immobility—designed to examine aspects of wildlife spatial activity and behavior not possible with conventional tracking systems. Application of these four routines to the real‐time monitoring of 94 African elephants was made. We also provide details of our cloud‐based monitoring system including infrastructure, data collection, and customized software for continuous tracking data analysis. We also highlight future directions of real‐time collection and analysis of biological, physiological, and environmental information from wildlife to encourage further development of needed algorithms and monitoring technology. Real‐time processing of remotely collected, animal biospatial data promises to open novel directions in ecological research, applied species monitoring, conservation programs, and public outreach and education.